Transforming the West Sumatra Police Hall: Retrofitting Strategies for a Multifunctional Facility - Sahputra, Deded Eka (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The West Sumatra Regional Police Hall, initially designed as an open sports facility without a roof, is repurposed into a multifunctional center for sports activities, social events, and disaster emergency response. The existing structure, a portal frame of reinforced concrete columns and beams, requires strengthening due to budget constraints that prevent its demolition and reconstruction. This study aims to evaluate the structural performance of the building after retrofitting to accommodate additional loads, including a truss frame and roof coverings. The jacketing method is used for column retrofitting, involving an increase in cross-sectional dimensions and additional reinforcement to enhance the structure’s strength and stiffness. Structural analysis shows that the original building lacks adequate capacity to withstand internal and external loads. Post-retrofitting, the analysis demonstrates significant improvements, including reduced shear forces and bending moments in columns and beams, minimized inter-level deflections, and compliance with column interaction diagrams. These enhancements ensure the building is structurally safe, particularly against seismic hazards, and capable of fulfilling its new functions. The findings highlight the effectiveness of the jacketing method for retrofitting and its potential application in similar structural repurposing projects.